2020
DOI: 10.1002/cpt.2080
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Landscape of New Drug Approval in Japan and Lags from International Birth Dates: Retrospective Regulatory Analysis

Abstract: The Pharmaceuticals and Medical Devices Agency (PMDA) has approved hundreds of new drugs in recent years. We retrospectively analyzed the new drugs approved in Japan from 2008 to 2019, and identify the first-in-world approvals and clarify the current drug lag. The new drug and the drug lag were defined as a drug with a new active substance and a difference between the approval date in Japan and the international birth date, respectively. Among 400 new drugs approved in Japan during the last 12 years, 80 (20.0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 28 publications
(81 reference statements)
2
33
0
Order By: Relevance
“…Although Sakigake thus requires the will to achieve the first‐in‐world approval in Japan, the system is also open to global sponsors. In this study, 1/4 of the sponsors for Sakigake products were from overseas, and this proportion was higher than that for the new drugs with first‐in‐approval in Japan, 6 suggesting that overseas manufacturers actively use this system. Sakigake, as well as BTD in the USA and PRIME in the EU, does not exclude the overlap designations.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Although Sakigake thus requires the will to achieve the first‐in‐world approval in Japan, the system is also open to global sponsors. In this study, 1/4 of the sponsors for Sakigake products were from overseas, and this proportion was higher than that for the new drugs with first‐in‐approval in Japan, 6 suggesting that overseas manufacturers actively use this system. Sakigake, as well as BTD in the USA and PRIME in the EU, does not exclude the overlap designations.…”
Section: Discussionmentioning
confidence: 65%
“…(C) The number of new drugs and the median drug lags from the international birth dates in each therapeutic area (with >8 products) among the drugs with new active substances approved in Japan from 2008 to 2019. The data in this panel of the Figure are not actually from this paper but from prior work 6 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug lag is a critical issue for patients with lifethreatening diseases or serious conditions that could cause irreversible disease progression [5,8]. For pediatric and/or rare diseases, there is an even higher risk of delay in drug approval in Japan, which further prolongs the drug lag [9].…”
Section: Data Source and Analysesmentioning
confidence: 99%
“…We have recently studied new drugs with Japan‐first approvals 7 and found that several new drugs required a long review period. Some important issues may underlie the review history for new drugs with delays in approval times.…”
Section: Introductionmentioning
confidence: 99%